Development of Interactive Digital Books to Improve Students' Academic Integrity and Its Implications for Guidance and Counseling Services - Yulitri, Rina; Jumiarti, Desri; Hardi, Emeliya; Febriyanti, Zahara (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research produces a product in the form of an interactive digital book that can be used by teachers, parents and students to improve students' academic integrity. The aim of this research is to determine the level of suitability of digital book products in improving academic integrity, and to determine the level of practicality of these digital book products. This development research refers to the steps developed by Thiagarajan through the 4-D method, namely the define stage, design stage and develop stage. The test subjects in this research were MAN 1 Padang City students. Based on the research results, the following results were obtained: first, this development research produced an interactive digital book for Madrasah Aliyah students who had gone through the validation test stage, in the module format aspect it was declared valid with an average of 0.88, in the module presentation aspect it was declared valid with an average of 0.88. The average is 0.9, and the material aspect of the module is declared valid with an average of 0.87, thus digital book i is declared valid. Second, this development research produced an interactive digital book that had gone through the practicality test stage for guidance and counseling teachers who obtained an average percentage of 88.75% in the very practical category, and student responses with an average percentage of 83.89% in the very practical category.